Towards background independent quantum gravity with tensor models - Eichhorn, Astrid; Koslowski, Tim Andreas; Lumma, Johannes; Duarte Pereira Junior, Antônio (Arxiv, 2018)
We explore whether the phase diagram of tensor models could feature a pregeometric, discrete and a geometric, continuum phase for the building blocks of space. The latter are associated to rank